2013
DOI: 10.3109/14992027.2013.840933
|View full text |Cite
|
Sign up to set email alerts
|

D-methionine pre-loading reduces both noise-induced permanent threshold shift and outer hair cell loss in the chinchilla

Abstract: D-met administration in advance of noise-exposure, without further administration, significantly protects from noise-induced ABR threshold shift and OHC loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Increased levels of ROS and RNS are present and active in the cochlea after continuous noise exposure [17][18][19]. Numerous antioxidant and pro-antioxidant compounds have been used to reduce the stress in the cochlea induced by ROS and/or RNS, subsequently protecting against NIHL [20][21][22][23][24][25][26][27][28]. These studies extend the studies that showed increased ROS and/or RNS formation in the cochlea after noise by confirming that the molecules are key factors in cochlear damage and resulting hearing loss from noise.…”
Section: Cochlear Pathology In Nihlsupporting
confidence: 64%
See 1 more Smart Citation
“…Increased levels of ROS and RNS are present and active in the cochlea after continuous noise exposure [17][18][19]. Numerous antioxidant and pro-antioxidant compounds have been used to reduce the stress in the cochlea induced by ROS and/or RNS, subsequently protecting against NIHL [20][21][22][23][24][25][26][27][28]. These studies extend the studies that showed increased ROS and/or RNS formation in the cochlea after noise by confirming that the molecules are key factors in cochlear damage and resulting hearing loss from noise.…”
Section: Cochlear Pathology In Nihlsupporting
confidence: 64%
“…Antioxidant compounds [20][21][22][23][24][25][26][27][28], glutamate antagonists [56], calcium channel blockers [57], JNK inhibitors [58,59] and glucocorticoid compounds [57,60] have all demonstrated protective or therapeutic effects against NIHL, and do not represent an exhaustive list of the classes of compounds that have been tested. Src inhibitors have clearly demonstrated a potential protective effect when the compound is delivered directly into the cochlea.…”
Section: Discussionmentioning
confidence: 97%
“…One cochlea per animal was assessed. This technique has been documented and utilized in previous publications (Campbell et al, 1996(Campbell et al, , 2007(Campbell et al, , 2011Claussen et al, 2013;Fox et al, 2015).…”
Section: Ohc Quantificationmentioning
confidence: 97%
“…D-methionine (D-met) is an otoprotectant tested to successfully prevent permanent cisplatin-, and noise-induced hearing loss in animals (Korver et al, 2002;Clifford et al, 2011;Campbell et al, 1996;2007;Claussen et al, 2013) D-met has also demonstrated otoprotection from gentamicin-, tobramycin-, and amikacin-induced ototoxicity without antimicrobial interference (Sha & Schacht, 2000;Campbell et al, 2007;Fox et al, 2015). As a sulfhydryl antioxidant, D-met may neutralize free radical formation, prevent cochlear oxidative stress, and protect from kanamycin-induced hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, dose-dependent protective effects of D -methionine have been reported in guinea pigs with NIHL (125-15 kHz, broad band white noise at 105 dB SPL) when the compound was administered at doses of 200, 400, and 600 mg/kg IP (Lo et al 2013 ). At around the same time, another report from a laboratory that has generated a signifi cant volume of D -methionine literature in NIHL described that when D -methionine was administered prior to noise exposure in chinchillas, hearing thresholds (measure by ABR recordings) were signifi cantly improved (Claussen et al 2013 ).…”
Section: Nihl and Antioxidantsmentioning
confidence: 99%